Identificación de espacios inundables mediante evaluación multicriterio y sistemas de información geográfica en la cuenca del Río Chone, provincia Manabí. - García, Julio (Machala : Universidad Técnica de Machala, 2024)
This research work deals with the multi-criteria evaluation and geographic information systems for the identification of floodplains in the Chone river basin, Manabí province, in which zones susceptible to flooding are established. This study was carried out using geotechnologies, the ArcGIS 10.4.2 program was used as the main tools for the processing and analysis of the information; as well as the official cartography. The methodology began with the selection of the variables considering all the aspects that can be related to the physical environment, their importance in the development of the phenomenon and the availability of official digital cartographic information (shapefile) for the study area. The variables chosen were: slope of the terrain, permeability, geoform, size of the materials with which the index maps were elaborated under the Universal Transverse Mercartor projection (UTM), georeferenced to the WGS84 datum for zone 17S, then for the superposition of variables, a relative weight was assigned to each variable indicator in order to obtain the weighted specific susceptibility map.Both the variables and the indicators were assigned relative values ​​according to their importance using the additive compensatory technique which is based on the Method of Analytical Hierarchies of Multicriteria Evaluation, this method proposes the use of a contrast matrix between pairs, where the number of rows and columns will be determined by the variables or indicators to be weighted; which will be compared to define if one has greater weight than the other (aij), and then proceed to determine the eigenvector which is the main vector establishing the weights (wj) and the eigenvalue that creates a quantitative measure of the correspondence of the value judgments between pairs of variables or indicators. The susceptibility maps were obtained from the previous reclassification of the indicators. At the end of the previous stage, the final susceptibility map was created once the relative weights had been assigned according to expert judgment, a modified algorithm was designed.
La investigación trata sobre Identificación de espacios inundables mediante evaluación multicriterio y sistemas de información geográfica en la cuenca del río Chone, provincia Manabí. En el que se establecen zonas susceptibles a inundaciones, se realizó mediante el uso de geotecnologías, la principal herramienta para el procesamiento y análisis de la información fue el programa ArcGIS 10.4.2; así como la cartografía digital oficial.La investigación inició con la selección de las variables considerando los aspectos que se relacionan con el medio físico, su importancia en el desarrollo del fenómeno y la disponibilidad de información cartográfica digital oficial (shapefile) para el área de estudio.Las variables seleccionadas fueron: pendiente del terreno, permeabilidad, geoforma, talla de los materiales, con los cuales se elaboraron los mapas índices bajo la proyección Universal Transversa de Mercartor (UTM), georreferenciada al datum WGS84 zona 17S, para la superposición de las variables, se adjudicó un peso relativo a cada indicador para así obtener el mapa de susceptibilidad específica ponderada. Tanto a las variables como a los indicadores se les asignaron valores relativos a la técnica compensatoria aditiva la cual está basada en el Método de las Jerarquías Analíticas de la Evaluación Multicriterio, el cual propone el uso de una matriz de contraste entre pares, en donde el número de filas y columnas estará determinado por las variables o indicadores a ponderar; las cuales se compararon para definir si una tiene mayor peso que la otra (aij), para luego pasar a determinar el eigenvector el cual es el vector principal estableciendo los pesos (wj) y el eigenvalor que crea una medida cuantitativa de la correspondencia de los juicios de valor entre pares de variables o indicadores.
Keywords: GEOTECNOLOGÍAS; EVALUACIÓN MULTICRITERIO; ARCGIS